Comparison of immediate breast reconstruction after mastectomy and mastectomy alone for breast cancer: A meta-analysis. Issue 2 (February 2017) - Zhang, P.; Li, C.-Z.; Wu, C.-T.; Jiao, G.-M.; Yan, F.; Zhu, H.-C.; Zhang, X.-P.
Abstract: Background: The purpose of this study was to compare patient outcomes between immediate breast reconstruction (IBR) after mastectomy and mastectomy alone. Methods: We conducted a comprehensive literature search of PUBMED, EMBASE, Web of Science, and Cochrane Library. The primary outcomes evaluated in this review were overall survival, disease-free survival and local recurrence. Secondary outcome was the incidence of surgical site infection. All data were analyzed using Review Manager 5.3. Results: Thirty-one studies, involving of 139, 894 participants were included in this paper. Pooled data demonstrated that women who had IBR after mastectomy were more likely to experience surgical site infection than those treated with mastectomy alone (risk ratios 1.51, 95% CI: 1.22–1.87; p  = 0.0001). There were no significant differences in overall survival (hazard ratios 0.92, 95% CI: 0.80–1.06; p  = 0.25) and disease-free survival (hazard ratios 0.96, 95% CI: 0.84–1.10; p  = 0.54) between IBR after mastectomy and mastectomy alone. No significant difference was found in local recurrence between two groups (risk ratios 0.92, 95% CI: 0.75–1.13; p  = 0.41). Conclusions: Our study demonstrates that IBR after mastectomy does not affect the overall survival and disease-free survival of breast cancer. Besides, no evidence shows that IBR after mastectomy increases the frequency of local recurrence.